Roles of RecJ, RecO, and RecR in RecET-Mediated Illegitimate Recombination in Escherichia coli - Shiraishi, Kouya (American Society for Microbiology, 2002)
We analyzed effects of overexpression of RecE and RecT on illegitimate recombination during prophage induction in Escherichia coli and found that frequencies of spontaneous and UV-induced illegitimate recombination are enhanced by coexpression of RecE and RecT in the wild type, but the enhanced recombination was reduced by recJ, recO, or recR mutation. The results indicated that RecET-mediated illegitimate recombination depends on the functions of RecJ, RecO, and RecR, suggesting that the RecE and RecJ exonucleases play different roles in this recombination pathway and that the RecO and RecR proteins also play important roles in the recombination. On the other hand, the frequency of the RecET-mediated illegitimate recombination was enhanced by a recQ mutation, implying that the RecQ protein plays a role in suppression of RecET-mediated illegitimate recombination. It was also found that RecET-mediated illegitimate recombination is independent of the RecA function with UV irradiation, but it is enhanced by the recA mutation without UV irradiation. Based on these results, we propose a model for the roles of RecJOR on RecET-mediated illegitimate recombination.